Cultivable Psychrotolerant Yeasts Associated with Antarctic Marine Sponges - Levican-Jaque, G; Martinez-Fernandez, C; Chavez-Rosales, R; Paillavil-Navarro, B (2013)
Unlike filamentous fungi and bacteria, very little is known about cultivable yeasts associated with marine sponges, especially those from Antarctic seas. During an expedition to King George Island, in the Antarctica, samples of 11 marine sponges were collected by scuba-diving. From these sponges, 20 psychrotolerant yeast isolates were obtained. Phylogenetic analyses of D1/D2 and ITS rRNA gene sequences revealed that the marine ascomycetous yeast Metschnikowia australis is the predominant organism associated with these invertebrates. Other species found belonged to the Basidiomycota phylum: Cystofilobasidium infirmominiatum, Rhodotorula pinicola, Leucosporidiella creatinivora and a new yeast from the Leucosporidiella genus. None of these yeasts have been previously associated with marine sponges. A screening to estimate the ability of these yeasts as producers of extracellular enzymatic activities at several pH and temperature conditions was performed. Several yeast isolates demonstrated amylolytic, proteolytic, lipolytic or cellulolytic activity, but none of them showed xylanolytic activity under the conditions assayed. To our knowledge, this work is the first description of cultivable yeasts associated with marine sponges from the Antarctic sea. © 2012 Springer Science+Business Media B.V.